Penapisan Bakteri Asam Laktat dari Susu Fermentasi Bermerek Yang Dijual di Pasar Swalayan Jalan Setiabudi Medan - Rahmiati, Rahmiati; Situmorang, Toberni S.; Simanjuntak, Helen Anjelina; Ratna A.K Marpaung, Dwi (Mahesa Research Center, 2023)
Lactic acid bacteria are a group of gram-positive bacteria that are able to ferment carbohydrates and produce lactic acid as a result of their metabolism. Lactic acid bacteria can be found naturally in the digestive tract of animals and plants. Apart from that, lactic acid bacteria are also used as a starter in the fermentation process. One of the fermented products that is processed using lactic acid bacteria is fermented milk, also known as yoghurt. Fermented milk is marketed under various trademarks. This research aims to characterize lactic acid bacteria isolates from branded fermented milk sold in supermarkets. The research was carried out using a qualitative descriptive method with stages namely sample preparation, isolation and characterization. Screening for lactic acid bacteria uses pour plate and streak plate methods. The results of the research showed that three isolates of lactic acid bacteria were obtained from the samples tested with different macroscopic characteristics, namely SFB01, SFB02 and SFB03. These three isolates were gram positive bacilli.